Adaptação de trajes masculino para mulheres: estilo tomboy - Rissi, Flávia Eloise Matos (2017)
The present study is situated at the intersection of theoretical fields of clothing history and the emergence of masculine dresses among women. It is to do a research on the history of women who have experienced changes in clothing, before, during and after World War II, and through this study, to develop differentiated products according to the chosen public. Using bibliographical researches and questionnaires to carry out the same, it is sought to identify the representation of the male costume used in women's clothing, reflected in the history and fashion changes.